Studies on Complexes of Rare Earths with Furohydroxamic Acid - Singh, Shikha; Kumar Singh, Sanjay; Singh, S.C.; Dhakarey, Rajesh (Asian Journal of Chemistry, 2010)
The complexes of Pr(III), Eu(III), Gd(III), Dy(III) and Yb(III) with furohydroxamic acid (FHA) have been characterized by elemental analysis, magnetic susceptibility measurements, IR and electronic spectral studies. The IR spectra suggest bidentate behaviour of the furohydroxamic acid. A coordination number seven is proposed around the metal ions with capped octahedron geometry of the complexes.